Overcoming covid-19 pandemic : Nietzsche’s Übermensch and the filipino notion of Magpakatao - Galeon, Alvin A. (Penerbit Universiti Kebangsaan Malaysia, 2022)
Driven by the pathological situation caused by this COVID-19 pandemic, this paper discusses the human ideal as argued by Nietzsche in his concept of the Übermensch (Superman). It also exposes the Filipino’s yearning to live the human ideal through “magpakatao” (to be human). Using textual analysis, I attempt to see the similarities and the differences between Nietzsche’s Übermensch and the Filipinos’ “magpakatao” in order to come up with a synthesized and better concept of human ideal. To be Superman, Nietzsche encourages one to live life on earth to the fullest by rejecting inter alia, Christianity. Opposed to Nietzsche, Filipinos need to surrender themselves to Bathala (God) which at times hinder them live this material world to the fullest in Nietzsche’s sense. However, this paper concludes the relevance of Nietzsche’s philosophy to reconstruct the Filipino notion of “magpakatao.” With this reconstructed notion of human perfectibility, I believe Filipinos and people all over the world could overcome any challenges that will come in their lives and still live and authentic and meaningful life amid this pandemic.